Design and evaluation of a digital learning environment for computer architecture education: A mixed methods case study - Janvier, Ngnoulaye (Journal for Teaching and Education for Scholars, 2026)
Teaching computer science to secondary school students in Cameroon presents significant pedagogical challenges due to insufficient teaching resources and a shortage of qualified teachers. This study presents the design, development, and evaluation of an educational software environment - SimuArch - specifically adapted for teaching computer architecture in class (Year 3 of lower secondary school) in Cameroon. Using a mixed-methods research design, this study combines a quantitative quasi-experimental approach with qualitative inquiry. An experimental evaluation involving 115 students - divided into an experimental group (n = 58) using SimuArch and a control group (n = 57) following standard instruction - was conducted over an 8-week period. Quantitative data were analysed using repeated-measures analysis of variance (ANOVA) and independent-samples t-tests; qualitative data were subjected to inductive thematic analysis. Results showed a statistically significant Group × Time interaction (F(1,113) = 24.8, p < 0.001, η² = 0.18; Cohen's d = 1.21), with an average performance gain of 75% in the experimental group compared to 35% in the control group. Qualitative analysis revealed a marked increase in student motivation and engagement. These findings suggest that integrating a contextually appropriate digital learning environment can significantly improve the teaching and learning of computer architecture at the secondary level in Cameroon, with potential implications for other sub-Saharan African educational contexts.